6th ANNUAL ASCOPE LABORATORY TEST CORRELATION - Bustani Mustafa (Testing Center for Oil and Gas LEMIGAS, 1988)
In ASEAN we have the ASCOPE correlation programme on CFR engine laboratory to obtain precision data in the gasoline by CFR test research method. Member countries taking part in the 6th Laboratory test correlation program for CFR engine are Indonesia as coordinator with seven laboratories participating, Malaysia with one laboratory, Philippines and Thailand with two laboratories each, Singapore and USA with one laboratory each.